Ustawa o zniewagach z 28 grudnia 1831 r. Wielkiego Księstwa Badenii - Nieciecka, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The subject of the article is the Act on Insults of 1831 of the Grand Duchy of Baden. The discussion of the Act’s content was preceded by an analysis of the legal status in this field since 1803 until the introduction of the Act and the presentation of its genesis. Baden became the first German- -language country which regulated the issue of protection of honour in a separate act. Moreover, Baden introduced a qualified form of violation in this area, committed against or by persons connected with the bureaucratic apparatus. Libertarian tendencies and provisions of the Act that were their manifestation contributed to the increase in the number of court proceedings in this rega
Keywords: Wielkie Księstwo Badenii; wielki książę Leopold; 1831; zniewaga; krzywda; fałsz; honor; ochrona honoru; prawo karne; procedura przystąpienia